First karyotype description of Epiplatys spilargyreius (Duméril, 1861) with comments on chromosome evolution in the genus Epiplatys Gill, 1862 (Nothobranchiidae) - Sergey A. Simanovsky; Alexandra Yu. Skuratovskaya; Margarita G. Simonian; Dmitry A. Medvedev; Fekadu Tefera; Alexander S. Golubtsov (Comparative Cytogenetics)
The African non-annual killifish genus Epiplatys Gill, 1862 (family Nothobranchiidae) comprises 36 valid species distributed in West, Central and East Africa. The available cytogenetic information for the genus indicates a wide variability in diploid chromosome number (2n) and number of chromosome arms (FN). Here, we report the karyotype of Epiplatys spilargyreius (Duméril, 1861), one of the two species with the lowest diploid chromosome number (2n = 34) in the genus, from the White Nile basin in Ethiopia. Male and female karyotypes contained 18 metacentric/acrocentric and 16 subtelocentric/acrocentric chromosomes. The number of chromosome arms is, respectively, FN = 52. Analysis of karyotype differentiation in the genus allowed us to suggest that the 2n reduction in E. spilargyreius and many other members of the genus Epiplatys is mainly due to Robertsonian translocations (reduction of 2n from 48 to 34 with stable NF = 48–52). We provide an up-to-date summary of cytogenetic data and a brief review of chromosome evolution in the genus.